1
$\begingroup$

Let $ V \ $ be a n-dimensional vector space over the field $ \ \mathbb{F} \ $ and let $ \ G \ $ be a non-degenerate billinear form on $ \ V \ $. Thus the map $ \ L_G : V \to V^{*} \ $ is a linear Isomorphism.

(a) Let $ \ \mathcal{B}=\{e_1,e_2,......, e_n \} \ $ be a basis of $ \ V \ $ . Using $ \ L_G \ $ , show that there exists a basis $ \ \mathcal{B}'=\{e_1',e_2',......, e_n' \} \ \ of \ \ V $ such that $ \ G(e_i,e_j')=\delta^i_j \ $

(b) For any $ \ v \in V \ $ , show that $ \ v=\sum_{i=1}^{n} G(v,e_i')e_i \ $

(c) For any $ \ v \in V \ $ , show that $ \ v=\sum_{i=1}^{n} G(e_i,v)e_i' \ $

where $ \ V^{*} \ $ is the dual space of $ \ V \ $

I need only part (c)

Answer:

(a)

Since $ \ L_G \ : \ V \to V^{*} $ is a isomorphism , then $ \ \{L_G(e_1), L_G(e_2),......., L_G(e_n) \} \ $ is a basis of $ \ V^{*} \ $ such that $ \ L_G (e_i)(e_j')=G(e_i,e_j')=\delta^i_j \ \ , \ 1 \leq i,j \leq n $

(b)

Let $ v \ $ be any vector in $ \ V \ $ , then $ \ V \ $ can be written as

$ v=c_1e_1+c_2e_2+........+c_ne_n \ , ...........(1) $ , where $ \ c_i \in \mathbb{F} \ $ for each $ \ 1 \leq i \leq n \ $

Then,

Operating $ \ L_G \ $ on both side , we get

$ L_G(v)=c_1L_G(e_1)+c_2L_G(e_2)+....+c_jL_G(e_j)+.....+c_n L_G(e_n) \\ \Rightarrow L_G(v)(e_j')=c_j L_G(e_j)(e_j') \\ \Rightarrow G(v,e_j')=c_j \delta^j_j=c_j \ \ , \forall j \\ \Rightarrow c_j=G(v,e_j'), ...............(2) $

From (1) and (2) , we get

$ v=G(v,e_1')e_1+G(v,e_2')e_2+.........+G(v,e_n')e_n \\ \Rightarrow v=\sum_{i=1}^{n} G(v,e_i')e_i $

(c)

Proceeding in the same way as in part (b)

$e_i=c_1e_1'+....+c_ie_i'+........c_ne_n' \ $

Operating $ L_G \ $ on both side , we get

$ L_G(e_i)=c_1 L_G(e_1')+........+c_i L_G(e_i')+........+c_n L_G(e_n') \\ \Rightarrow L_G(e_i)(v)=c_1 L_G(e_1')(v)+.......+c_iL_G(e_i')(v)+.....+c_n L_G(e_n')(v) $

But Now I can not finish the proof

Help me finishing the proof

$\endgroup$
  • 1
    $\begingroup$ Let $v =\sum v_j' e_j'$. Then $G(e_i,v) = G(e_i, \sum v_j' e_j') = \sum _{j} v_j' G(e_i,e_j') = \sum_jv_j' \delta_{ij} = v_i'$. So $v = \sum_i G(e_i,v) e_i'$ $\endgroup$ – Sou Jun 26 '18 at 14:07

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.